Food word processing in Chinese reading: A study of restrained eaters. - Luo, Changlin; Zhu, Mengyan; Zhuang, Xiangling; Ma, Guojie (British Journal of Psychology, 2023)
Food‐related attentional bias refers that individuals typically prioritize rewarding food‐related cues (e.g. food words and food images) compared with non‐food stimuli; however, the findings are inconsistent for restrained eaters. Traditional paradigms used to test food‐related attentional bias, such as visual probe tasks and visual search tasks, may not directly and accurately enough to reflect individuals' food‐word processing at different cognitive stages. In this study, we introduced the boundary paradigm to investigate food‐word attentional bias for both restrained and unrestrained eaters. Eye movements were recorded when they performed a naturalistic sentence‐reading task. The results of later‐stage analyses showed that food words were fixated on for less time than non‐food words, which indicated a superiority of foveal food‐word processing for both restrained and unrestrained eaters. The results of early‐stage analyses showed that restrained eaters spent more time on pre‐target regions in the food‐word valid preview conditions, which indicated a parafoveal food‐word processing superiority for restrained eaters (i.e. the parafoveal‐on‐foveal effect). The superiority of foveal food‐word processing provides new insights into explaining food‐related attentional bias in general groups. Additionally, the enhanced food‐word attentional bias in parafoveal processing for restrained eaters illustrates the importance of individual characteristics in studying word recognition.